Posterior rehabilitation using 3D-printed dental implants and synthetic regenerative biomaterials - Lopes, Guilherme da Rocha Scalzer [UNESP]; de MATOS, Jefferson David Melo [UNESP]; Oliveira, Dayane; Prado, Pedro Henrique Condé Oliveira [UNESP]; Rocha, Mateus Garcia; Sinhoreti, Mário Alexandre Coelho; Bottino, Marco Antonio [UNESP]; Ramos, Nathália de Carvalho (Editora Cubo, 2022)
Aim: To describe through a clinical case report the surgical sequence of rehabilitation with 3D-printed implants associated with maxillary sinus floor lift with synthetic regenerative materials, including biphasic bioceramic. Case Report: Patient had an agenesis of the upper left premolars (#12 and #13), a vertical bone deficiency caused by maxillary sinus’ pneumatization, and a horizontal alveolar resorption around the missing teeth area. During the surgical procedures, incisions, detachment, and osteotomy were performed in the lateral region of the maxillary sinus. The sinus membrane was detached and lifted 10 mm. Then, a thick poly(dioxanone)-based synthetic resorbable membrane (Plenum) was inserted and adapted inside the sinus to protect the sinus membrane. After the osteotomies with sub-instrumentation, 3D-printed implants (Plenum) were installed in the #12 area (3.5mm x 11.5 mm; 30N) and #13 area (4.0mm x 10mm; 20N). The maxillary sinus was entirely filled with a biphasic bioceramic, HA/β-TCP (70:30) 500-1000 μm (Plenum) and covered by the same synthetic resorbable membrane. Connective tissue graft from the palatal area was positioned internally to the flap and stabilized with sutures to improve the vestibular tissue architecture. The entire surgical wound was sutured, and the tissues stabilized. No complications occurred in the postoperative period. Conclusion: The use of synthetic regenerative memberane and 3D-printed implants seems to be a promising option in areas of deficient bone remnants.
Reabilitação posterior com implantes impressos e biomateriais sintéticos
Keywords: 3D Printing; Dental Implants; Maxillary Sinus; Sinus Floor Augmentations; Tissue Grafting